PROFIL PRESTASI AKADEMIK SISWA AHLI DAN SISWA PEMULA DALAM PEMBELAJARAN FISIKA SMA YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Triyana Dewi; Irma Rahma Suwarma; Asep Sutiadi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Model cooperative learning type Jigsaw is a learning model that divide students into expert and novice group. Expert’s students give an explanation of subtopics experts to novice student in the novice group, therefore with model cooperative learning type jigsaw students can be more interactive and get maximal value of academic performance. The purpose of this study was to describe about profile academic performance of expert and novice student in the cooperative learning type jigsaw. The samples of this study consisted of 34 students at a high school in Bandung. The one group pretest-posttest experiment design was chosen in conducting the research. The data was analysed using an anlaysis descriptive methode and retrieval of data was taken using multiple choice instrument test of 15 item at pre-test and post-test. The results showed that academic performance of expert student higher than novice student. Analysed from the gain of pre-test to post-test. Academic performance of expert student increase g = 0,42 at the medium category and academic performance of novice student increase g = 0,32 at the medium category. With the result that model cooperative learning type jigsaw can increase academic performance of expert as well as novice student. Keywords: Cooperative Learning type Jigsaw, expert and novice student, academic performance.